Options trading activity and firm valuation - Roll, Richard; Schwartz, Eduardo; Subrahmanyam, Avanidhar (Journal of Financial Economics, 2009)
Options may have an effect on firm value because they help complete markets and stimulate informed trades. However, these benefits are likely to manifest themselves in active, rather than inactive, options markets. Supporting this observation, we find that firms with more options trading have higher values of Tobin's q, after accounting for other determinants of value. Corporate investment in firms with greater options trading is more sensitive to stock prices. Options trading affects firm valuation more strongly in stocks with greater information asymmetry. These results indicate that options trading is positively associated with firm values as well as information production.